Characterization of finite groups with some S-quasinormal subgroups of fixed order - Asaad, M. (Algebra and Discrete Mathematics, 2012)
Let G be a finite group. A subgroup of G is said to be S-quasinormal in G if it permutes with every Sylow subgroup of G. We fix in every non-cyclic Sylow subgroup P of the generalized Fitting subgroup a subgroup D such that 1 < |D| < |P| and characterize G under the assumption that all subgroups H of P with |H| = |D| are S-quasinormal in G. Some recent results are generalized.